Environmental drivers of microbial community shifts in the giant barrel sponge, Xestospongia muta, over a shallow to mesophotic depth gradient. (15th February 2016) - Morrow, Kathleen M.; Fiore, Cara L.; Lesser, Michael P.
Summary: The giant barrel sponge, X estospongia muta, is a high microbial abundance sponge found on Caribbean coral reefs along shallow to mesophotic depth gradients where multiple abiotic factors change with depth. Sponges were collected along a depth gradient at Little Cayman (LC) and Lee Stocking Island (LSI), and the microbiome of these samples was analysed using 16S rRNA amplicon sequencing. Statistically significant shifts in community structure and dissimilarity (∼ 40%) were detected from 10 to 90 m in LC sponges, but a similar shift was not identified in sponges from 10 to 60 m at LSI (only 17% dissimilar). Additionally, inorganic nutrient levels steadily increased with depth at LSI but not at LC. Based on bulk stable isotopic variability, sponges collected from LC were generally more enriched in 15 N and less enriched in 13 C as depth increased, suggesting a transition from dependency on photoautotrophy to heterotrophy as depth increased. Patterns of stable isotopic enrichment were largely invariant at LSI, which is also reflected in the more stable microbial community along the depth gradient. It appears that environmental factors that change with depth may contribute to differences in X . muta microbial assemblages, demonstrating the importance of contemporaneous environmental sampling in studies of the microbiome of sponges.